(untitled) (American Journal of Islam and Society, 1992)
There is a point of view popular with some religious thinkers-among them Muslims-that religion and morality are two separate institutions and have very little to do with each other. This is because the former is centered in God, while the latter is entirely human in content and approach. According to this view, an individual can be moral without subscribing to any recognizable religion. Furthermore, a deeply religious person occupies a station in life where usual relations with the world, including those with other people, are perceived as being so lowly and mundane that they become irrelevant. This is, to say the least, not the essential Qur’anic standpoint. The Qur’an , as well as a number of sayings of the Prophet, does not envisage an estrangement between God and humanity. Human beings are said to have been created after the image of God: Who is nearer to each person than hisher own jugular vein (Qur’an 50:16). They a so close to each other that they may possibly enter into a mutual dialogue. There is thus an organically intimate relevance of the individual’s religious faith with the subsequent performance of the corresponding moral actions. In the Qur’an, the word amanu (they held on to faith [in God]) is almost invariably followed by ‘amilu al salihat (they performed good actions). However, it must be undelstood that faith is not an honorific term, a characteristic that may be inculcated into an person’s character in its own right. It rather refets to a barely psychological state, an attitude of mind A person may have faith in the all-good God or in some evil being(s) (Qur’an 4:31). In the first case, such an individual is necessarily good, in the other, he/she is bound to be morally bad ...